Ondansetron Exposure Changes in a Pregnant Woman. Issue 9 (25th July 2016) - Lemon, Lara S.; Zhang, Hongfei; Hebert, Mary F.; Hankins, Gary D.; Haas, David M.; Caritis, Steve N.; Venkataramanan, Raman
Abstract : Pregnancy results in many physiologic changes that can alter the pharmacokinetic profiles of medications used during pregnancy. One of the primary factors leading to these pharmacokinetic changes is altered activity of drug‐metabolizing enzymes. Ondansetron is a substrate of cytochrome P450 (CYP) 3A4 (primary metabolic pathway), 2D6, and 1A2, all of which are altered during pregnancy. We evaluated the pharmacokinetics of ondansetron at three different gestational time points in a 26‐year‐old, pregnant, Caucasian woman with normal liver and kidney function, who was maintained on ondansetron 8 mg administered orally 3 times/day throughout her pregnancy. Serial plasma samples were collected from the subject over one 8‐hour dosing interval at 14, 24, and 35 weeks' gestation (representing early‐, mid‐, and late‐pregnancy time points, respectively). Ondansetron plasma concentrations were determined using liquid chromatography–tandem mass spectrometry. Ondansetron area under the plasma concentration–time curve decreased progressively across gestation (634 ng hr/ml in early pregnancy, 553 ng hr/ml in mid‐pregnancy, and 387 ng hr/ml in late pregnancy), with a corresponding increase in apparent oral clearance (12.6 L/hr in early‐pregnancy, 14.5 L/hr in mid‐pregnancy, and 20.7 L/hr in late‐pregnancy). The decreased area under the plasma concentration–time curve and exposure to ondansetron across gestation is likely due to increased activity of CYP3A4 and CYP2D6 during pregnancy. We were not able to study this patient during the postpartum period; however, as with other CYP3A4 and CYP2D6 substrates, the apparent activities of these isoenzymes are likely return to baseline. To our knowledge, this is the first report to describe ondansetron pharmacokinetics across gestation. Additional pharmacokinetic and pharmacodynamic data are needed to confirm our results and to evaluate clinical impact; however, in the meantime, clinicians should be aware of these pharmacokinetic changes in ondansetron exposure during pregnancy.